2006
DOI: 10.1080/10910340600713554
|View full text |Cite
|
Sign up to set email alerts
|

Forces and Temperatures in Hard Turning

Abstract: & In precision machining, due to the recent developments in cutting tools, machine tool structural rigidity and improved CNC controllers, hard turning is an emerging process as an alternative to some of the grinding processes by providing reductions in costs and cycle-times. In industrial environments, hard turning is established for geometry features of parts with low to medium requirements on part quality. Better understanding of cutting forces, stresses and temperature fields, temperature gradients created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The difference in terms of error is less than 7.7% for surface roughness and less than 6.9% for main cutting force. It proves that the model and equation generated give a fair reading indicating a reasonable model as per the previous study by Lazoglu et al [21]. The results obtained also validated the reliability of the model.…”
Section: Confirmation Experimentssupporting
confidence: 85%
“…The difference in terms of error is less than 7.7% for surface roughness and less than 6.9% for main cutting force. It proves that the model and equation generated give a fair reading indicating a reasonable model as per the previous study by Lazoglu et al [21]. The results obtained also validated the reliability of the model.…”
Section: Confirmation Experimentssupporting
confidence: 85%
“…When thermal aspects are coupled with mechanical aspects, this will result in rapid tool wear. Tool wear, not only reduces the tool life and increases the machining costs, but it also increases the forces and tensile residual stresses affecting the surface quality and causing white layer surface damages [7]. These generated white layers possess a negative effect on surface finish and fatigue strength of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that precision hard turning has many advantages compared with grinding, such as short cycle time, process flexibility, reasonable surface finish, higher material removal rate and lesser environment problems without the use of cutting fluid [2][3][4]. On the other hand, Lazoğlu et al [5] have shown that early tool wear, tool breakage, chipping, tool stresses, cutting temperatures, residual stresses, white layer phenomena, machined surface quality and surface integrity are very important issues in hard machining industrial applications.…”
Section: Introductionmentioning
confidence: 99%